Toward sustainability of territorial agro-food systems in Europe: indicators for assessing alternative scenarios - Josette Garnier; Gilles Billen (Environmental Research Letters)
Describing territorial agro-food systems through nitrogen flows between agriculture, livestock farming, human consumption, and external trade represents a useful basis for assessing the environmental sustainability of these systems. The concepts of circularity and self-sufficiency are often put forward in assessments to complement indicators related to environmental impacts, such as nitrogen use efficiency, environmental N surplus, N losses. Here, we use these indicators to assess the environmental performance and sustainability of the agro-food systems of 127 regions in Europe in their current state as well as under two alternative scenarios of varying degrees of structural changes designed to reach sustainability. Both scenarios consider the projected European population at 2050, a dietary change toward less animal protein (30% and 20%, instead of 57% for the reference situation, Ref 2015–2019) and are based on the widespread use of organic crop rotations and the banning of synthetic fertilizers and feed imports. An Agro-Ecology scenario (AE) exploits crop and livestock production at optimal production capacity in the current agricultural areas of each region, thus maintaining the possibility of external trade, while a Radical Simplicity of lifestyle scenario (RS), limits production to regional requirements, with excess agricultural land set aside for reforestation and rewilding. AE and RS are able to feed Europe and greatly reduce environmental losses (more than 50% for both scenarios), but some not self-sufficient regions still necessitate interregional exchanges. Full circularity is theoretically not possible; it increases from 30% (Ref) to 43% (AE). At the European scale, N-food self-sufficiency remains over 1 (2.6 for Ref, 1.6–1.2 for AE and RS), while import dependency of European regions on commercial N-import for food delivery, currently over 2.7 as a mean, drops below 0.1 in both scenarios. The results illustrate the complex relationships between self-sufficiency, circularity, and the environmental impact of territorial agro-food systems.